A vision of corporate social responsibility in the context of the COVID-19 pandemic - Mora Tufino, Michael Meliton (Universidad Ciencia y Tecnología, 2022)
Over time, the vision of Corporate Social Responsibility has been expanding around the world among the big corporate groups. Within which many are applying distorted concepts of social responsibility in the development of their organizational policies. Although there are various conceptual currents and patterns of CSR, the generalization of the approach has generated benefits both for companies and the environment, their workers, communities of the social environment, and nations in general. The strategic visions of Corporate Social Responsibility were known from the previous, present, and post-pandemic moments for business consortiums and the effectiveness of the corporate social responsibility approach in promoting educational campaigns to use biosecurity measures, people agglomeration control measures, and other strategies joint public and private sector to deal with the COVID 19 pandemic.